2010
DOI: 10.1111/j.1467-9566.2009.01222.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Not the swab!’ Young men’s experiences with STI testing

Abstract: In Canada, STI rates are high and rising, especially amongst young men.Meanwhile, the needs of young men regarding STI testing services are poorly understood, as are the socio-cultural and structural factors that influence young men's sexual health-seeking behaviours. To better understand this phenomenon, we draw on interviews with 45 men (ages 15-25) from British Columbia, Canada. Our research reveals how structural forces (e.g. STI testing procedures) interact with socio-cultural factors (e.g. perceptions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
78
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 53 publications
5
78
0
Order By: Relevance
“…For example, getting tested for sexually transmitted infections (STI) or HIV can be perceived as potentially emasculating experiences for young men (Duck, 2009;Knight et al, 2012Knight et al, , 2013, exposing them to clinical encounters in which their sexuality, sexual identity and sexual behaviour may be 'interrogated' and, in some situations, their bodies 'inspected' (e.g., genital exams) (Shoveller et al, 2010. While some research has also identified factors that may 'motivate' men to seek testing (e.g., a sexual experience they consider to be 'high risk', the beginning or end of a sexual relationship, experiencing symptoms) (Shoveller et al, 2010;Katz et al, 2013), there has been very little empirical research regarding the extent to which young men's HIV testing practices may be influenced by normative considerations, including notions of responsibility/obligation to Self, as well as various relational considerations to Others.…”
Section: Young Men and Hiv Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, getting tested for sexually transmitted infections (STI) or HIV can be perceived as potentially emasculating experiences for young men (Duck, 2009;Knight et al, 2012Knight et al, , 2013, exposing them to clinical encounters in which their sexuality, sexual identity and sexual behaviour may be 'interrogated' and, in some situations, their bodies 'inspected' (e.g., genital exams) (Shoveller et al, 2010. While some research has also identified factors that may 'motivate' men to seek testing (e.g., a sexual experience they consider to be 'high risk', the beginning or end of a sexual relationship, experiencing symptoms) (Shoveller et al, 2010;Katz et al, 2013), there has been very little empirical research regarding the extent to which young men's HIV testing practices may be influenced by normative considerations, including notions of responsibility/obligation to Self, as well as various relational considerations to Others.…”
Section: Young Men and Hiv Testingmentioning
confidence: 99%
“…Within and across many global settings, voluntary HIV testing participation rates among young men remain disproportionately low compared to other population subgroups (Shoveller et al, 2010, Knight et al, 2013. Given the public health imperative to enhance HIV testing rates among those unaware of their seropositive status, young men represent a population of particular importance as expanded HIV testing initiatives unfold (e.g., scaling up of routine HIV testing practices).…”
Section: Introductionmentioning
confidence: 99%
“…16 Concerns about invasive testing, such as swabs or examinations, also impede testing. 17 Similarly, being asked one's sexual health history (i.e., when clinicians ask about sexual contacts) makes some persons, primarily sexual minorities, less willing to undergo testing. 18,19 Other barriers relate to health care provider behaviour, such as judgemental attitudes or limited knowledge -for instance, when clinicians do not offer HIV testing when persons, particularly sexuallyactive MSM, present for care with HIV seroconversion symptoms (e.g., rash, fever, fatigue, flu-like symptoms).…”
mentioning
confidence: 99%
“…17,19 For men to undergo testing, they must reject norms about masculinity, which dictate that they should be autonomous and invulnerable. 17 Often during testing, however, men follow a clinician's direction, and by simply accessing testing, must admit that they could have an infection and thus that they are vulnerable. Taken as a whole, therefore, the reasons people do not access STI/HIV testing are 1) a lack of desire to do so (whether this relates to lack of concern, feelings of immunity, or incomplete understandings) and/or 2) an inability to obtain the STI/HIV testing they seek.…”
mentioning
confidence: 99%
See 1 more Smart Citation